Development of radiographic classification criteria for hand osteoarthritis: a methodological report (Phase 2). Issue 1 (4th February 2022) - Haugen, Ida K; Felson, David; Abhishek, Abhishek; Berenbaum, Francis; Edwards, John James; Herrero Beaumont, Gabriel; Hermann-Eriksen, Merete; Hill, Catherine L; Ishimori, Mariko; Jonsson, Helgi; Karjalainen, Teemu; Leung, Ying Ying; et al.
Abstract : Objectives: In Phase 1 of developing new hand osteoarthritis (OA) classification criteria, features associated with hand OA were identified in a population with hand complaints. Radiographic findings could better discriminate patients with hand OA and controls than clinical examination findings. The objective of Phase 2 was to achieve consensus on the features and their weights to be included in three radiographic criteria sets of overall hand OA, interphalangeal OA and thumb base OA. Methods: Multidisciplinary, international expert panels were convened. Patient vignettes were used to identify important features consistent with hand OA. A consensus-based decision analysis approach implemented using 1000minds software was applied to identify the most important features and their relative importance influencing the likelihood of symptoms being due to hand OA. Analyses were repeated for interphalangeal and thumb base OA. The reliability and validity of the proposed criteria sets were tested. Results: The experts agreed that the criteria sets should be applied in a population with pain, aching or stiffness in hand joint(s) not explained by another disease or acute injury. In this setting, five additional criteria were considered important: age, morning stiffness, radiographic osteophytes, radiographic joint space narrowing and concordance between symptoms and radiographic findings. The reliability and validity were very good. Conclusion: Radiographic features were considered critical when determining whether a patient had symptoms due to hand OA. The consensus-based decision analysis approach in Phase 2 complemented the data-driven results from Phase 1, which will form the basis of the final classification criteria sets.